Persecuting Alex Rodriguez: Race, money and the ethics of reporting the performance-enhancing drug scandal. (2nd January 2016) - Brennen, Bonnie; Brown, Rick
Abstract : This qualitative textual analysis considers the US press coverage of Alex Rodriguez for his alleged use of performance-enhancing drugs. It evaluates nearly 500 newspaper, magazine and broadcast reports from 2007 to 2014 on Rodriguez, as well as reader and journalistic responses, and finds issues of overt and inferential racism, stereotyping and symbolic impurity, and a crude emphasis on money in the coverage. This research considers the ethics of the press coverage through a framework of Critical Race Theory and suggests an approach rooted in communitarian ethics to foster greater social justice and balance in sports media coverage.